PEMBELAJARAN BAHASA DAERAH BERBASIS KEARIFAN LOKAL DALAM KONTEKS KURIKULUM MERDEKA PADA SEKOLAH DASAR NEGERI 006 SANGAT UTARA - Nurbaya, annisa oktaviani; Nazwa Syifa Maulida; Elva Restu Rahayu; Anjany Putri Belawati Pandiagan (Prodi PGMI IAI Darul Ulum Kandangan, 2025)
In the context of cultural globalization, the preservation and revitalization of local languages have become essential for maintaining regional identity and heritage. This study aims to examine the use of the Kutai language in extracurricular activities at SD Negeri 010. Employing a qualitative approach, that involved teachers, the vice principal for curriculum, and students as subjects. Data was collected through observation, interviews, and documentation. The findings showed that the Kutai language is taught as a tool to introduce local culture and character values. Although there is no specific extracurricular program dedicated to the Kutai language, cultural activities and social media are utilized as alternative means for its preservation. This learning not only brings students closer to their local culture but also strengthens their cultural identity. Keywords: Socializing efforts, local languages, extracurricular activities.